2021
DOI: 10.1002/humu.24221
|View full text |Cite
|
Sign up to set email alerts
|

Common polymorphic OTC variants can act as genetic modifiers of enzymatic activity

Abstract: Understanding the role of common polymorphisms in modulating the clinical phenotype when they co-occur with a disease-causing lesion is of critical importance in medical genetics. We explored the impact of apparently neutral common polymorphisms, using the gene encoding the urea cycle enzyme, ornithine transcarbamylase (OTC), as a model system. Distinct combinations of genetic backgrounds embracing two missense polymorphisms were created in cis with the pathogenic p.Arg40His replacement. In vitro enzymatic ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
(148 reference statements)
0
5
0
Order By: Relevance
“…A high-throughput functional assay of all single nucleotide variant (SNV)-accessible amino acid replacements in human OTC revealed that around 5% of all OTC variants have up to 30% higher activity than wild-type human OTC [ 65 ]. Furthermore, human OTC with two common p.R46K and p.Q270R sequence variants had 40% higher enzymatic activity than the wild-type or either of the single mutant proteins [ 66 ]. Therefore, we hypothesize that some of the NAGS, CPS1, and citrin missense variants found in tumors can increase the activity of mutant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A high-throughput functional assay of all single nucleotide variant (SNV)-accessible amino acid replacements in human OTC revealed that around 5% of all OTC variants have up to 30% higher activity than wild-type human OTC [ 65 ]. Furthermore, human OTC with two common p.R46K and p.Q270R sequence variants had 40% higher enzymatic activity than the wild-type or either of the single mutant proteins [ 66 ]. Therefore, we hypothesize that some of the NAGS, CPS1, and citrin missense variants found in tumors can increase the activity of mutant proteins.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is the fact that we have only analyzed the coding region, and thus we could not rule out the hypothesis of the existence of mutations in the non-coding regions of those genes being associated with this mRNA reduction. A previous work has shown that apparently neutral polymorphic variants can modulate the clinical phenotype [ 53 ], and likely could interfere with mRNA expression. Another, possible explanation is that it could be due to a phenomenon similar to transcriptional adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of cis -related genetic heterogeneity can underlie incomplete penetrance, allelic imbalance, and compensatory effects among other phenomena ( Cooper et al, 2013 ; Lopes-Marques et al, 2021 ; Serrano et al, 2021 ). Several studies have shown that the rs1805124 variant is able to act as a genetic modifier of many SCN5A disease-associated variants ( e.g .…”
Section: Discussionmentioning
confidence: 99%
“…Mendelian monogenic diseases often show clinical heterogeneity, so that individuals carrying the same variant can manifest different phenotypes. This may result from epistatic interactions between variants highlighting the importance of the genetic background in the phenotypic characteristics each individual manifests ( Fournier & Schacherer, 2017 ; Lehner, 2011 ; Lopes-Marques et al, 2021 ; Suriano et al, 2007 ). The importance of genetic architecture is well illustrated in the particular case of co-occurrence of polymorphic and deleterious variants in the same protein.…”
Section: Introductionmentioning
confidence: 99%